An Eternal Repetition? The Category of Time in the Works of Elena Dolgopyat - Trojanowska, Urszula (Slavia Orientalis, 2020)
In Dolgopyat’s works, the world appears as an inscrutable mystery in which the wonderful and supernatural is closely connected with the realistic and everyday. Probably the most important part of this universe is chronotope. In this article, I focus on the category of time in selected stories in which it comes to the foreground. „The heroes of the analyzed stories travel in time, stop time or look for an answer to the question of the originality of their experiences. After all, if one can go back in time, maybe the whole of life is a mere repetition of what has already happened?”. Transitions between various time levels open up the way to other worlds and variants of one’s own destiny. The magical properties of time show that the reality of the heroes is not limited to matter and does not fit into the rationalistic picture of the world. This confirms the affiliation of the works to magical realism.
Keywords: magical realism; Elena Dolgopyat; contemporary Russian literature; time; space